Issues of developing financial technologies in Vietnam in modern conditions - Hung Ninh Le; O. B. Anikin (Вестник университета)
The use of digital technology in finance has led to the creation of more efficient and convenient financial services at lower costs, providing customers with a more attractive experience than traditional financial services. This trend has become dominant in recent decades, but it is a relatively new field in Vietnam. Vietnam has great potential for financial technology (hereafter referred to as fintech) development: the young population is increasingly using digital technologies in their daily lives, and the country has a relatively developed telecommunications and e-commerce infrastructure. However, fintech in Vietnam also faces many challenges, such as information technology risks, increased competition in the financial institution market, and difficulties in non-banking organizations management and supervision. Coordination among government agencies, fintech businesses and citizens is needed to address these challenges. The government needs to improve legal policy, raise public awareness, and create favorable conditions for fintech development. Fintech companies need to improve their products and services quality to meet people’s needs. The population needs to be aware of financial technologies to be able to effectively use fintech products and services.